Hepatocellular carcinoma in situs inversus totalis-a case report (Medical Journal of Indonesia, 2014)
A 43-year old male presented with persistent discomfort and pain upper abdomen (epigastrium) more on left side associated with fever on and off, along with fatigue and loss of appetite for the last four months. Physical examination revealed mass on left hypochondrium extending to epigastrium with mild distension of the abdomen. Imaging studies of the patient showed dextrocardia on chest x-ray postero-anterior (PA) view, thoracic and abdominal CT scan showed situs inversus totalis with multiple SOL (space occupying lesion) in right lobe of liver with largest measuring 8x6 cm2 in the 4th segment. USG-guided FNAC of the mass showed features of hepatocellular carcinoma. Thereupon, hepatocellular carcinoma in situs inversus totalis was diagosed to this patient and was clinically staged as T3aN0M0. He was given sorafenib 400 mg orally twice daily with an advice to come for regular assessment every 4 week. Keywords: hepatocellular carcinoma, situs inversus totalis, case report